2016
DOI: 10.1007/s00330-016-4257-y
|View full text |Cite
|
Sign up to set email alerts
|

Added value of CT perfusion compared to CT angiography in predicting clinical outcomes of stroke patients treated with mechanical thrombectomy

Abstract: • CBV-ASPECTS is a significant predictor of clinical outcome. • Single phase CTA-ASPECTS has low predictive value. • Using CBV-ASPECTS, raters identified futile reperfusions in 96 % of the cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…The American Heart Association (AHA) guidelines 2019 do not recommend perfusion imaging in the early (0‐6 hours) window 15 . However, recent studies have suggested that advanced neuroimaging‐based selection for thrombectomy nearly doubles the probability of good functional outcomes as compared to minimalistic approach of CT/CTA‐based selection 16‐18 . All the patients in EXTEND‐IA and 80% of the patients in SWIFT PRIME, were enrolled based on the target mismatch profile on perfusion imaging 6 .…”
Section: Discussionmentioning
confidence: 99%
“…The American Heart Association (AHA) guidelines 2019 do not recommend perfusion imaging in the early (0‐6 hours) window 15 . However, recent studies have suggested that advanced neuroimaging‐based selection for thrombectomy nearly doubles the probability of good functional outcomes as compared to minimalistic approach of CT/CTA‐based selection 16‐18 . All the patients in EXTEND‐IA and 80% of the patients in SWIFT PRIME, were enrolled based on the target mismatch profile on perfusion imaging 6 .…”
Section: Discussionmentioning
confidence: 99%
“…The underlying reasons are not clear. It could be analyzed, for instance, whether there is also a correlation of T max ASPECTS (at a delay of >8 or 10 s) with clinical outcome (Tsogkas et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The latter is evaluated by applying ASPECTS to maps of the cerebral blood volume (CBV) gathered with CTP [11]. Cut-off for an EVT in the 6 to 12 hour time window is a CBV-ASPECTS of 6 and above.…”
Section: Methodsmentioning
confidence: 99%